Français écrit – français parlé - Gorilovics, Tivadar (Verbum – Analecta Neolatina, 2005)
The opposition between written and spoken language is particularly conspicuous in French. The issue can be approached from various angles and at various levels. This paper discusses the problems of (standard) usage as well as the representation of the spoken language with a special emphasis on the age of romanticism and realism (Balazac, Monnier, Zola, Maupassant, Courteline). 20th-century poets and artists will also be considered (Barbusse, Céline and Raymond Queneau). The paper highlights the use of certain tenses (imparfait du subjonctif, passé simple) in French because of their practical and literary importance.